Music, Neuroscience, and the Psychology of Well-Being: A Précis - Croom, Adam M. (Frontiers in Psychology, 2012)
In Flourish, the positive psychologist Martin Seligman (2011) identifies five commonly recognized factors that are characteristic of human flourishing or wellbeing: (1) “positive emotion,” (2) “relationships,” (3) “engagement,” (4) “achievement,” and (5) “meaning” (p. 24). Although there is no settled set of necessary and sufficient conditions neatly circumscribing the bounds of human flourishing (Seligman, 2011), we would mostly likely consider a person that possessed high levels of these five factors as paradigmatic or prototypical of human flourishing. Accordingly, if we wanted to go about the practical task of actually increasing our level of wellbeing, we ought to do so by focusing on practically increasing the levels of the five factors that are characteristic of wellbeing. If, for instance, an activity such as musical engagement can be shown to positively influence each or all of these five factors, this would be compelling evidence that an activity such as musical engagement can positively contribute to one’s living a flourishing life. I’m of the belief that psychological research can and should be used, not only to identify and diagnose maladaptive psychological states, but identify and promote adaptive psychological states as well. In this article I advance the hypothesis and provide supporting evidence for the claim that musical engagement can positively contribute to one’s living a flourishing life. Since there has not yet been a substantive and up-to-date investigation of the possible role of music in contributing to one’s living a flourishing life, the purpose of this article is to conduct this investigation, thereby bridging the gap and stimulating discussion between the psychology of music and the psychology of wellbeing.